Cardiovascular responses to leg-press exercises during head-down tilt - Alessandro, Cristiano; Sarabadani Tafreshi, Amirehsan; Riener, Robert (Frontiers in Sports and Active Living, 2024)
Introduction Physical exercise and gravitational load affect the activity of the cardiovascular system. How these factors interact with one another is still poorly understood. Here we investigate how the cardiovascular system responds to leg-press exercise during head-down tilt, a posture that reduces orthostatic stress, limits gravitational pooling, and increases central blood volume. Methods Seventeen healthy participants performed leg-press exercise during head-down tilt at different combinations of resistive force, contraction frequency, and exercise duration (30 and 60 s), leading to different exercise power. Systolic (sBP), diastolic (dBP), mean arterial pressure (MAP), pulse pressure (PP) and heart rate (HR) were measured continuously. Cardiovascular responses were evaluated by comparing the values of these signals during exercise recovery to baseline. Mixed models were used to evaluate the effect of exercise power and of individual exercise parameter on the cardiovascular responses. Results Immediately after the exercise, we observed a clear undershoot in sBP (Δ = −7.78 ± 1.19 mmHg), dBP (Δ = −10.37 ± 0.84 mmHg), and MAP (Δ = −8.85 ± 0.85 mmHg), an overshoot in PP (Δ = 7.93 ± 1.13 mmHg), and elevated values of HR (Δ = 33.5 ± 0.94 bpm) compared to baseline (p < 0.0001). However, all parameters returned to similar baseline values 2 min following the exercise (p > 0.05). The responses of dBP, MAP and HR were significantly modulated by exercise power (correlation coefficients: rdBP = −0.34, rMAP = −0.25, rHR = 0.52, p < 0.001). All signals’ responses were modulated by contraction frequency (p < 0.05), increasing the undershoot in sBP (Δ = −1.87 ± 0.98 mmHg), dBP (Δ = −4.85 ± 1.01 and Δ = −3.45 ± 0.98 mmHg for low and high resistive force respectively) and MAP (Δ = −3.31 ± 0.75 mmHg), and increasing the overshoot in PP (Δ = 2.57 ± 1.06 mmHg) as well as the value of HR (Δ = 16.8 ± 2.04 and Δ = 10.8 ± 2.01 bpm for low and high resistive force respectively). Resistive force affected only dBP (Δ = −4.96 ± 1.41 mmHg, p < 0.0001), MAP (Δ = −2.97 ± 1.07 mmHg, p < 0.05) and HR (Δ = 6.81 ± 2.81 bpm, p < 0.0001; Δ = 15.72 ± 2.86 bpm, p < 0.0001; Δ = 15.72 ± 2.86 bpm, p < 0.05, depending on the values of resistive force and contraction frequency), and exercise duration affected only HR (Δ = 9.64 ± 2.01 bpm, p < 0.0001). Conclusion Leg exercises caused only immediate cardiovascular responses, potentially due to facilitated venous return by the head-down tilt position. The modulation of dBP, MAP and HR responses by exercise power and that of all signals by contraction frequency may help optimizing exercise prescription in conditions of limited orthostatic stress.